2016
DOI: 10.1246/cl.151035
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Organosulfonium Electrophiles as Unique Reagents for Carbon–Sulfur Bond Formation: Prospects in Synthetic Chemistry of Organosulfur Compounds

Abstract: Carbonsulfur (CS) bond formation is one of the important synthetic routes in organic chemistry. Among sulfur sources for CS bond formation, organosulfur cations (RS + ) and their synthetic equivalents are unique reagents. These cationic sulfur species are easily prepared as compared with the oxonium analogues, because of their low ionization potentials. This review describes various synthetic methods for CS bond formation, mainly focusing on electrophilic reactions, addition to olefins, and substitution to aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 71 publications
0
13
0
1
Order By: Relevance
“…30 In conclusion, the results of these ESI-MS experiments suggest that (a) diselanes are most likely regenerated under oxidative conditions from intermediates of type 4, potentially through the mechanism illustrated in Scheme 2 (scenario b), and (b) triselenonium species (ArSe) 3 + and related polyselenonium cations may likely be operative intermediates in the catalytic cycle. It is important to point out that, in contrast to sporadic reports on olefin functionalizations mediated by trisulfonium cations [(ArS) 3 ] + , 28,31 cognate triselenonium cations have so far not been generally considered as catalytically active intermediates in analogous SET oxidation processes on the basis of experimental results but rather the corresponding monomeric selenenium electrophiles (RSeY). 9a,42 To validate the hypothesis that triselenonium cations may lead to the very same intermediates and products that were observed under photocatalytic conditions (i.e., intermediates 4 and products 2; cf.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…30 In conclusion, the results of these ESI-MS experiments suggest that (a) diselanes are most likely regenerated under oxidative conditions from intermediates of type 4, potentially through the mechanism illustrated in Scheme 2 (scenario b), and (b) triselenonium species (ArSe) 3 + and related polyselenonium cations may likely be operative intermediates in the catalytic cycle. It is important to point out that, in contrast to sporadic reports on olefin functionalizations mediated by trisulfonium cations [(ArS) 3 ] + , 28,31 cognate triselenonium cations have so far not been generally considered as catalytically active intermediates in analogous SET oxidation processes on the basis of experimental results but rather the corresponding monomeric selenenium electrophiles (RSeY). 9a,42 To validate the hypothesis that triselenonium cations may lead to the very same intermediates and products that were observed under photocatalytic conditions (i.e., intermediates 4 and products 2; cf.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, these halogen-based strategies often suffer from narrow substrate scope or heavy metal contaminations of products. To avoid such problems, significant efforts have been devoted to invent C–H sulfanylation of arenes under metal-free conditions. , However, previous methods entirely focused on Friedel–Crafts-type reactions of arenes with electrophilic sulfur reagents or their precursors, i.e., N -sulfanylsuccinimides, disulfides, thiols, and so on . Consequently, harsh reaction conditions and/or highly electron-rich arenes such as anilines, phenols, and indoles have been required (Scheme A).…”
mentioning
confidence: 99%
“…Poly(2,6-dimethyl-1,4phenylenesulfide) (PMPS) and poly(2-methoxy-1,4-phenylenesulfide) (OMePPS) were prepared according to a previous report. 12,15 Measurements 1 H and 13 C NMR spectra were obtained using a JEOL ECX500 spectrometer (500 Hz), and the samples for NMR experiments were prepared by adding tetramethylsilane (TMS) as an internal standard. The molecular weights of polymers were determined using a SHIMADZU CBM-20A and SPD-20MA, with a TOSOH TSKgel SuperHM-N column (eluent: chloroform or DMF (containing 0.1 M LiCl), flow rate: 0.3 mL min −1 ).…”
Section: Reagentsmentioning
confidence: 99%
“…Our group found that poly(phenylene sulfide) (PPS), regarded as one of the super engineering plastics with high crystallinity and thermal stability, became completely amorphous once it was derivatized with alkyl or alkoxyl side groups. [11][12][13][14][15][16][17] These PPS derivatives presented not only good solubility in organic solvents, but also high transparency and high RI, all of which were suitable for optical applications.…”
Section: Introductionmentioning
confidence: 99%